PENERAPAN MODEL ANALYSIS, FINDINGS, DEVELOPMENT, ORGANIZING THE MATERIAL AND LEARNING UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA - Apdoludin Apdoludin; Umi Lestari; Zulqoidi R Habibie (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The main problems in this study were students who were not active in learning, students who were unable to solve problems independently, students who were unable to analyze learning material in depth, and teachers who had not used the right learning model so that it had an impact on student learning processes and outcomes. This research was conducted on fourth-grade students at SDN 217/II Bangun Harjo Pelepat Ilir Bungo, Jambi, Indonesia. The method used is classroom action research (CAR). The subjects in this study consisted of 18 students, 10 girls, and 8 boys. The technique used for data collection is an interview, observation, tests, and documentation techniques. The research instrument uses test sheets and observation sheets. The results of the study are that by using the Analysis, Findings, Development, Organizing the Material and Learning model in PKN learning it can improve the process and results of PKN learning for class IV students at SDN 217/II Bangun Harjo.